Cobalt Blue - Reilly, Matthew (Pan Macmillan Australia, 2022)
For 35 years, the United States and Russia each had their own superhero. Three days ago, America's hero died. Today will be bad. In the face of an overwhelming attack, one young woman-unassuming and anonymous-might be America's only hope. Her codename ... COBALT BLUE.